2022
DOI: 10.3390/nu14153195
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gut Microbiota Enterotypes with Blood Trace Elements in Women with Infertility

Abstract: Infertility is defined as failure to achieve pregnancy within 12 months of unprotected intercourse in women. Trace elements, a kind of micronutrient that is very important to female reproductive function, are affected by intestinal absorption, which is regulated by gut microbiota. Enterotype is the classification of an intestinal microbiome based on its characteristics. Whether or not Prevotella-enterotype and Bacteroides-enterotype are associated with blood trace elements among infertile women remains unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…In our MR analysis, both Bacteroides and Bacteroidaceae showed protective effects on male fertility, indicating the potential role of Bacteroides in the management of infertile males. It has been found that Bacteroides might affect the iron metabolism in infertile females, highlighting the links between Bacteroides and reproductive function [ 33 ]. Several species of Bacteroides were detected to be correlated with non-obstructive azoospermia in male infertility [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our MR analysis, both Bacteroides and Bacteroidaceae showed protective effects on male fertility, indicating the potential role of Bacteroides in the management of infertile males. It has been found that Bacteroides might affect the iron metabolism in infertile females, highlighting the links between Bacteroides and reproductive function [ 33 ]. Several species of Bacteroides were detected to be correlated with non-obstructive azoospermia in male infertility [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous community properties of the gut microbiome suggest different metabolic function and responses to the same food in digestive tract, which may eventually influence the maternal and infant metabolism. Two enterotypes of gut microbiome were classified based on 651 Chinese pregnant women, which are separately dominated by Bacteroides , Prevotella ( Yao et al, 2022 ). Differences in taxonomic composition imply that enterotypes may differ in functional and ecological properties.…”
Section: Precise Management Of Nutrition and Health During Pregnancy ...mentioning
confidence: 99%